LARVICIDAL, PUPICIDAL AND SMOKE TOXICITY EFFECT OF KAEMPFERIA GALANGA TO THE MALARIAL VECTOR, ANOPHELES STEPHENSI - ABIRAMI DHANDAPANI,; SHOBANA KUMAR,; MURUGAN KADARKARAI, (The Bioscan, 2011)
Laboratory investigation have been made to test the larval and pupal toxicity, smoke toxicity and repellent potential of methanolic extract of Kempferia galanga at different concentrations (0.25%, 0.5%, 1.0%, 2.0% and 4.0%) against the different instar (I, II, III and IV) larvae and pupae of Anopheles stephensi. Methanolic extract of Kaempferia galanga showed considerable toxicity effect against larvae and pupae of Anopheles stephensi. Lethal concentration (LC50 and LC90) has been worked out on different larval stags of Anopheles stephensi. The LC50 and LC90 values of K. galanga for I instar larvae were 0.63 %,3.15 %, II instar 0.86 %, 3.66%, III instar 1.12%, 4.14%, IV instar 1.43%, 4.55%, respectively. The LC50 and LC90 values of pupae were 0.69%, 3.05%. Smoke toxicity effect also worked out on the adult mosquito of Anopheles stephens, the smoke emerged from Kaempferia galanga plant parts have considerably affected the adult mosquitoes and brought out considerable mortality and also treated adults laid minimum number of eggs. ,